Effect of Joint Flexibility on Seismic Performance of a Reinforced Concrete Ductile Moment-Resisting Frame - Dagvabazar Gombosuren; Takeshi Maki (Advances in Materials Science and Engineering)
Currently, the seismic collapse risk of modern code-conforming reinforced concrete (RC) frame structures is often evaluated without considering the behavior of the beam-column (BC) joints since joints designed to meet modern concrete design codes are assumed to be sufficiently rigid. BC joints in RC ductile moment frames may undergo a significant amount of inclined cracking during strong earthquakes. Consequently, the stiffness, strength, and dynamic characteristics of the RC moment frames may vary. Hence, the rigid joint assumption may be unsuitable for assessing the seismic performances of RC ductile moment frames because the local strength and ductility demands of the constituent members can be misinterpreted by structural analyses based on the assumption of a rigid joint. In this study, nonlinear static and dynamic analyses are conducted to quantify the seismic response variations of low- to midrise RC-frame structures under different joint modeling assumptions. In total, six 2D continuum finite element models of four- and eight-story frames with rigid and flexible joints were constructed by simulating the actual structures as realistically as possible. The results indicate that the interior joints in the considered frames suffer light-to-moderate damage, and the effect of joint cracking is found to be significant in a four-story structure whose column-to-beam flexural strength ratio and column-to-beam area ratio are below 1.5. Such joint behavior demonstrates that current code provisions cannot ensure joint behavior compatible with the rigid joint assumption that is used in the practical structural analysis of RC-frame buildings.